SISTEM SOSIAL JANTAN MONYET HITAM SULAWESI (Macaca nigra) DI CAGAR ALAM TANGKOKO-BATUANGUS, SULAWESI UTARA - Saroyo Saroyo (BERITA BIOLOGI, 2009)
A study on male social system of Sulawesi crested black macaque {Macaca nigra) has been conducted at Tangkoko-Batuangus Nature Reserve, North Sulawesi from January to October 2008.The aim of this research was to evaluate the male social system based on the social interaction among the males.The material was a habituated group called Rambo II that had 7 adult males and 19 adult females at early stage observation. Dominance hierarchy was determined with ad libitum sampling based on their results in agonistic interaction at 3 early-days of every month. The dynamics of the dominance hierarchy was traced during 10 months. Determination of dominance hierarchy linearity used Landau's index of linearity. Data of approaches among the males and their copulation frequency was collected with focal animal sampling.Approaches interaction data were analyzed for the direction of their approaches and the scoring of approachee responds that consisted of positive, neutral, negative, and without approaching.Results showed that during 10 months, there were 3 adult males that emigrated from Rambo II and one adult male that immigrated into the group.All dominance hierarchy had linearity indexes 1.0 that meant the hierarchies are perfect linear or linear and transitive.The a-male had highest frequency of copulation both with estrous and non-estrous females.For mid-rank male, on the other hand, the frequency was not always related to their rank. There was a tendency that dominate males approached subordinate males that was proved with their up/down index. Negative respond showed by subordinate males due to approaching by dominate ones was higher than the opposite. This result indicated that dominance played role in spatial controlling and freedom of interaction, for subordinate individual, the dominate presentating likely intimidated them. From those results, it can be concluded that the social system of male Sulawesi crested black macaque in not egalitarian and more despotic, different with the social system of the female that is considered as egalitarian.